Benefits on pain intensity, quality of life, and disability of women with dysmenorrhea undergoing general exercises versus Pilates: a pilot study - Peruzzo, Bruna Cristina Taques; Ramalho, Lisley Sousa; Figueiredo, Marta Regina; Alfieri, Fábio Marcon (ABCS Health Sciences, 2015)
Introduction: Primary dysmenorrhea is a gynecological disorder characterized by pain associated with menstruation without a pathological cause. Objective: To assess and compare pain intensity, disability and quality of life of women with primary dysmenorrhea undergoing general exercise versus Pilate’s method. Methods: This study included 14 women randomly assigned to general exercise (19.14±1 years) group and Pilates group (20.57±1.8 years). Both groups performed two sessions per week for 50 minutes over two and a half months, totaling 20 sessions. The general exercise group performed stretching and strengthening of the abdominal and lower back muscles, and of pelvic floor. The Pilates group, on the other hand, practiced exercises for pelvis awareness with contractions of transverse and abdomen rectus muscles, buttocks, perineum and erectors of spine. All the participants responded to the questionnaires of the Oswestry disability index for low back pain; Visual Analogue Scale (VSA) to measure pain intensity; and SF-36 Quality of Life Questionnaire before and after the intervention. Data were considered statistically significant when p<0.05. Results: Significant improvements after the intervention in both groups were found in all evaluations. With regard to the differences between the groups, in the item of low back pain disability, the general exercise group had better outcomes (p<0.003) than the Pilates group, as well as in the domain of health status (0.03) of the SF-36 Questionnaire. Conclusion: Practice of general exercises as well as Pilates’s method by women with dysmenorrhea can reduce pain and disability and improve the quality of life.